渐开线齿轮精确建模及齿根弯曲应力分析 - 李辉; 张世洪; 周常飞 (Jixie chuandong)
By means of the powerful 3Dgraphics capabilities of Pro/E,the accurate 3Ddiagram of involute modified spur gear is drawn.By importing the 3Dgear diagram into software ANSYS sharing good data exchange interface with Pro/E,the tooth root bending stress value is given by stress cloud diagram.